Polystrata alba from the Ninniyur formation of the Cauvery Basin, South India - Kishore, S.; Singh, S. K. (Ecoprint: An International Journal of Ecology, 2010)
The sediments of the Ninniyur formation (Paleocene) are characterized by exceptionally rich of calcareous algae. The present paper deals morphotaxonomical, palaeoecological and palaeogeographical aspects of the Polystrata alba (red algae). Polystrata alba (Pfender) Denizot is belonging to the family Peyssonneliaceae of the class Rhodophyceae. It is extent taxa, wide geographic distribution and known from early Cretaceous-Recent of the different part of the world. Key Words: Polystrata Alba; Palaeocene; Ninniyur; Formation; Cauvery Basin doi: 10.3126/eco.v12i0.3197 Ecoprint: An International Journal of Ecology 12: 59-63, 2005